Factors associated with geographic variation in cost per episode of care for three medical conditions - Jack Hadley; James D. Reschovsky; James A. O'Malley; Bruce E. Landon (Health Economics Review, 2014)
Objective: To identify associations between market factors, especially relative reimbursement rates, and the probability of surgery and cost per episode for three medical conditions (cataract, benign prostatic neoplasm, and knee degeneration) with multiple treatment options. Methods: We use 2004 - 2006 Medicare claims data for elderly beneficiaries from sixty nationally representative communities to estimate multivariate models for the probability of surgery and cost per episode of care as a function local market factors, including Medicare physician reimbursement for surgical versus non-surgical treatment and the availability of primary care and specialty physicians. We used Symmetry's Episode Treatment Groups (ETG) software to group claims into episodes for the three conditions (n = 540,874 episodes). Results: Higher Medicare reimbursement for surgical episodes and greater availability of the relevant specialists are significantly associated with more surgery and higher cost per episode for all three conditions, while greater availability of primary care physicians is significantly associated with less frequent surgery and lower cost per episode. Conclusion: Relative Medicare reimbursement rates for surgical vs. non-surgical treatments and the availability of both primary care physicians and relevant specialists are associated with the likelihood of surgery and cost per episode.
Keywords: 330; Medicare reimbursement; Geographic variation in Medicare cost per episode; Physician supply